Cupular growth rate of free neuromasts in three species of cyprinid fish - Mukai, Yukinori; Kobayashi, Hiroshi (Japanese Society of Fisheries Science, 1992)
The cupulae of cyprinid larval fish became deformed or disappeared by anesthesia in MS 222 solution, but when the larva was transferred to MS 222 free water, the cupulae began to grow again. The growth rate of newly extending cupulae was examined after treatment wish the MS 222 solution. The rates were 8.7-10.6 μm/h in Gnathopogon elongatus caerulescens, 10.3-11.3μm/h in Carassius auratus grandoculis, and 8.9μm/h in Zacco platypus. These findings suggest that complete replacement of the treated cupulae would take about 24h in the larvae of these species.